Analysis of the Role of Educational Games Ball Relay Puzzles in Improving the Cognitive Abilities of Early Childhood Children - Ilham Marito Setiaji; Amin Yusuf (Universitas Negeri Semarang, 2025)
Background – The importance of early childhood education in building the future. Early childhood is a crucial or golden period, so action needs to be taken in terms of education. The focus of this study is to describe the role of educational toys in developing the cognitive abilities of early childhood at Alam Jungle School Kindergarten. Research Urgency – Cognitive development in early childhood plays an important role in a child's future, so it is necessary to have learning methods that can optimise this cognitive development, such as learning using educational toys. Research Objectives – The purpose of this study was to describe how educational ball relay puzzle games can develop the cognitive abilities of young children at Alam Jungle School kindergarten. Research Method – This study utilised a descriptive qualitative method. Data collection techniques included interviews, documentation, and observation. Data validity techniques utilised triangulation of techniques and sources. Data analysis utilised data reduction, data presentation, and conclusion drawing. Research Findings – Based on the results of research conducted at Alam Jungle School Kindergarten, it was found that the use of educational games such as ball relay puzzles can develop children's cognitive abilities. However, there are several obstacles in the learning process using educational games, such as the availability of teaching aids and children's enthusiasm in participating in learning. Conclution – This study successfully described the role of educational ball relay puzzle games in developing the cognitive abilities of early childhood students at Alam Jungle School Kindergarten, including lesson planning, the learning process, the role of educational games, and supporting and inhibiting factors in the learning process. These educational games proved to play an important role in the effectiveness of learning and were able to develop the cognitive abilities of children at Alam Jungle School Kindergarten.